Viruses of the fall armyworm Spodoptera frugiperda: a review with prospects for biological control - Hussain, A.G.; Wennmann, J.; Goergen, Georg E.; Bryon, A.; Ros, V.I.D. (MDPI, 2021)
The fall armyworm (FAW), Spodoptera frugiperda, is a native pest species in the Western hemisphere. Since it was first reported in Africa in 2016, FAW has spread throughout the African continent and is now also present in several countries in Asia as well as Australia. The invasion of FAW in these areas has led to a high yield reduction in crops, leading to huge economic losses. FAW management options in the newly invaded areas are limited and mainly rely on the use of synthetic pesticides. Since there is a risk of resistance development against pesticides in addition to the negative environmental and human health impacts, other effective, sustainable, and cost-efficient control alternatives are desired. Insect pathogenic viruses fulfil these criteria as they are usually effective and highly host-specific with no significant harmful effect on beneficial insects and non-target organisms. In this review, we discuss all viruses known from FAW and their potential to be used for biological control. We specifically focus on baculoviruses and describe the recent advancements in the use of baculoviruses for biological control in the native geographic origin of FAW, and their potential use in the newly invaded areas. Finally, we identify current knowledge gaps and suggest new avenues for productive research on the use of viruses as a biopesticide against FAW.